STRATEGIES FOR DEVELOPING HUMAN RESOURCE CAPACITY IN EDUCATIONAL INSTITUTIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the theoretical and methodological foundations as well as modern strategies for developing human resource capacity in educational institutions. It analyzes approaches to enhancing teachers’ professional competencies, supporting innovative practices, integrating digital pedagogy, and implementing mentoring and coaching systems. The article also provides a scientific explanation of the criteria for assessing staff capacity and the role of monitoring and diagnostic processes in the development of educational organizations.